A Method of Developing the Overall Strength Quality of Young Wrestlers - Ochilov Rufat Qo`qonovich (Genius Publishing Group, 2022)
Today, the issue of training talented athletes in sports practice makes it necessary to take a new approach to the training process. This need is especially evident in the struggle. The fact that a large number of young people are engaged in wrestling is a modern requirement for the training process with young wrestlers in accordance with modern requirements. In particular, the development of general strength qualities in the training process of young wrestlers aged 9-10 is important and relevant.
Keywords: Young Wrestlers; Training Process; training; wrestlers